Real Thai cooking : recipes and stories from a Thai food expert - Nualkhair, Chawadee (Tuttle Publishing, 2023)
Learn the secrets of Thai cooking that only local foodies know about! Real Thai Cooking is a labor of love by Thailand's leading food blogger and street food expert, Chawadee "Chow" Nualkhair and Lauren Lulu Taylor, who did the recipe testing and editing and provided many of the photographs. Her book presents the full range of iconic Thai recipes together with fascinating back stories that enable you to truly appreciate what you are cooking and eating!